Carbohydrate feedings during team sport exercise preserve physical and CNS function - Winnick, J. J.; Davis, J. M.; Welsh, R. S.; Carmichael, M. D.; Murphy, E. A.; Blackmon, J. A. (Medicine & Science in Sports & Exercise, 2005)
Purpose: This study was designed to examine the effect of carbohydrate (CHO) feedings on physical and central nervous system (CNS) function during intermittent high-intensity exercise with physical demands similar to those of team sports such as basketball.